STRATEGI PARTAI DEMOKRAT DI TENGAH DOMINASI PARTAI LOKAL (Kajian pada Pemilihan Umum Tahun 2009 di Kota Banda Aceh, Provinsi Nanggroe Aceh Darussalam) - , Muhadi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Election 2009 in Banda Aceh City marked the victory of Partai Demokrat (P.D.) to gain 23 per cent (16.790) of total valid votes. This acquisition was followed by Partai Aceh as one of the dominant local parties with 14.134 votes (19.37%). This fact then raises a big question. How did PD able to win the legislative elections, while other local parties in Aceh has been so well-known. This study further investigating how the Partai Demokratâs strategies in winning the 2009 elections, especially in Banda Aceh city? through qualitative methods, the author attempted to answer these questions. Data sources or informants in this study were the managers of PD as well as political observers in Banda Aceh City. Data collection techniques were in-depth interviews, observation, and documentation. This study used primary data in form of informantsâ statement or action and secondary data was electionrelated data 2009 in Banda Aceh. Study results stated that PD in Banda Aceh City had used an offensive strategy in winning the election. Offensive strategy is different than defensive strategy which likely to 'surrender' and maintain a status quo. offensive strategy is pro-actively utilized the existing political resources. One source of political power which become PDâs mainstay is the figure of Susilo Bambang Yudhoyono (SBY) that is very popular in the eyes of the people of Indonesia, primarily in Banda Aceh. SBY as a powerful figure has managed to harness his power to lobby some high-level political elites of the Free Aceh Movement (GAM). Both were seen intimately, to the last 2009 Presidential election that GAM leaders were recruited to success the winning of SBY-Boediono team.